On Mann's Type Method for Nonexpansive and Strongly Quasinonexpansive Mappings in Hilbert Spaces. (2nd July 2015) - Hussain, Nawab; Marino, Giuseppe; Alamri, Badriah A. S.
Abstract : In the setting of Hilbert spaces, we study Mann's type method to approximate strong solutions of variational inequalities. We show that these solutions are fixed points of a nonexpansive mapping and/or a strongly quasinonexpansive mapping, depending on the coefficients involved in the algorithm.